Management of Islamic Propagation Activities in Building an Inclusive Religious Program at the Muslimin Mosque on Jalan STM Medan - Fadli Fadli; Hadi Saputra Panggabean (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: This study aims to explore three main aspects, namely the forms of da'wah management implemented, the challenges faced, and the strategies adopted to create inclusive religious programs that are accessible to all congregations. Methodology: The research employed a descriptive qualitative design with purposive site selection. Primary data were collected through in-depth interviews with mosque administrators, preachers, active congregants, and community leaders. Secondary data were gathered from administrative records and program documentation. Data analysis followed Miles and Huberman’s interactive model, which consists of data reduction, data display, and conclusion drawing. Main Findings: The findings indicate that da'wah activities function not only as religious gatherings but also as social learning arenas where congregants collectively negotiate values, identities, and intergroup relations. These activities are managed through systematic planning, congregation segmentation, diverse program implementation, and participatory evaluation. They also serve as a medium for interethnic interaction and cultural exchange that directly contribute to ethno-social pedagogy. Within this pedagogical space, local cultural wisdom and community-based religious understanding are integrated to strengthen inclusive learning processes. Ultimately, the management of da'wah in this context strengthens da'wah's role as a dynamic social learning arena that not only promotes inclusive religious education but also enriches ethno-social pedagogical practices that are essential for maintaining long-term social cohesion. Novelty/Originality of this study: This study provides evidence that Masjid Muslimin serves as a model of inclusive da’wah management in an urban context and demonstrates the potential of mosque-based religious governance to strengthen communal relations in multicultural settings. Its contribution lies in illustrating the socio-pedagogical value of structured da’wah management for enhancing inclusive participation among diverse Muslim congregants.